1977
DOI: 10.3171/jns.1977.46.4.0428
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mycotic intracranial aneurysms

Abstract: Two patients with mycotic intracranial aneurysms were successfully treated with only antibiotic therapy. One patient, who had subacute bacterial endocarditis, rheumatic valvular disease, and an abscessed tooth, sustained a subarachnoid hemorrhage from a ruptured right middle cerebral artery trifurcation aneurysm. The other patient, who had Turner's syndrome and probable congenital aortic stenosis, developed multiple neurological findings during an ipisode of acute bacterial endocarditis precipitated by an infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 28 publications
1
41
0
1
Order By: Relevance
“…Bingham 273 reported that ICMAs resolved between initial and follow-up angiography in 52% of patients treated with effective antibiotic therapy. A decrease in ICMA size was observed in an additional 29% of patients.…”
Section: Intracranial Masmentioning
confidence: 99%
“…Bingham 273 reported that ICMAs resolved between initial and follow-up angiography in 52% of patients treated with effective antibiotic therapy. A decrease in ICMA size was observed in an additional 29% of patients.…”
Section: Intracranial Masmentioning
confidence: 99%
“…135 Until more experience is gained with other imaging modalities, conventional angiography remains the diagnostic imaging test of choice. 129,135 ICMAs may heal with medical therapy: Bingham 136 reported that ICMAs resolved between an initial and follow-up angiogram in 52% of patients treated with effective antibiotic therapy. A decrease in ICMA size was seen in an additional 29%.…”
Section: Mycotic Aneurysmsmentioning
confidence: 99%
“…Antibiotics may cause histological changes in infectious aneurysm because complete resolution of bacterial intracranial aneurysms has occurred after antibiotic treatment in some cases. 6,19,20) Also, an obvious predisposing cardiac lesion was observed by echocardiography immediately after the first surgery in our patient.…”
Section: Discussionmentioning
confidence: 91%